The Role of Probiotics in Various Diseases - Rashid, Sulthan Al (International Journal of Human and Health Sciences (IJHHS), 2021)
We know that probiotics are found to be useful in various conditions like irritable bowel syndrome, opioid tolerance, indigestion, depression, anxiety, and ADHD. But still, we don’t know the proper mechanism involved in the treatment of these conditions by probiotics supplementation. In this Letter to Editor, I have written one interesting hypothesis which connects probiotics’ common mechanism of action to all these diseases. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 375-376